Pengaruh Pengawasan Camat Terhadap Pelaksanaan Tugas Kepala Desa Di Kecamatan Bacan Barat Utara Kabupaten Halmahera Selatan - Aya, Lewi; Rumapea, Patar; Plangiten, Novva (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: the influence of the supervision of the execution of the duties against the head of the villagehead is in fact the Act of comparing between planning with existing results. This is because between the twoof these frequent irregularities, then the task of supervision is make corrections over the irregularities.Issues that are questionable in this research is whether the Head could be influential in overseeing theimplementation of the village chief In North Halmahera Regency West Bacan Island South. Based ontheoretical studies indicate that theoretically a hypothesis of influence against the head of the supervision ofthe execution of the duties of the head of the village. The methods used in this research is quantitativemethods. The subject of this research is the apparatus of Government and society that is in the North Westwith Bacan Island Subdistrict total number of Village 8 villages. Research samples taken as many as 30people. Data collection is done using questionnaire and assisted with interview techniques. Analysistechniques that white is a linear regression analysis and correlation of product moment. Data analysisresults showed: (1) the regression coefficient of the variable head of surveillance against the execution of theduties of the head of the village is positive and real (2) coefficient of correlation and coefficient ofdetermination of the variable head of surveillance against the execution of the duties of the head of thevillage is situated on a high category. Based on these results it was concluded that the supervision of thehead of a positive and significant effect against the execution of the duties of the head of the village; Thismeans that the head of supervision is an important factor that determines the future of communitydevelopment. The conclusion left then suggested that "the execution of the duties of the head of a village indistrict of North Western bacan island still needs to have its increase, given the implementation and resultsof the programmes reached over this yet. Such efforts can be done ". with or through peaksanaan improvingthe quality of the leadership of the Head in the process of supervisionKeywords: head of Supervision and implementation of village chief